Community Service Through Beef Cattle Management Education at PT. Hasanuddin Agrivisi Internusa as an Effort to Improve the Knowledge of Local Breeders - Raihan; Marlina; La Ode M. Iskandar Z.; Rani Rahmadani; Tarmiji; Siti Jumairah; La Ode Muhammad Aswad Salam Salam (Majalah Pengabdian Indonesia, 2026)
This community service activity aims to improve the knowledge and technical skills of local farmers and university students regarding beef cattle management through education and field practice at PT. Hasanuddin Agrivisi Internusa. The three-day program, conducted through outreach, field demonstrations, and group discussions, focused on feed management, barn sanitation, and disease prevention in beef cattle. Results demonstrated an increase in participants' understanding and skills in nutritional management, balanced feed formulation, routine barn sanitation, and preventive health measures such as deworming. Field evaluations demonstrated increased awareness and responsibility in livestock management. This program significantly contributed to increasing the productivity of beef cattle and strengthened collaboration between universities, industry, and the community in developing sustainable livestock agribusiness.